Peningkatan Kemampuan Berpikir Kritis dan Hasil Belajar Bahasa Indonesia melalui Penerapan Model Project Based Learning - Sofianti Towif Khabiba; Akhwani Akhwani; Sianah Sianah (STKIP AL HIKMAH SURABAYA, 2023)
The aim of this research is to describe the learning process using a project-based learning model and to describe improving critical thinking skills using a project-based learning model. This research method is classroom action research with the Kemmis and Mc Taggart model research design which is applied through two cycles. This research consists of four stages, namely planning, action, observation and reflection. Data collection techniques are carried out through observation activities, evaluation tests and document review. The data analysis technique was carried out quantitatively descriptively. The research results showed that there was an increase in students' critical thinking skills and learning outcomes during the research. This is in line with the average value of critical thinking abilities which has increased after implementing project-based learning (PjBL). Thus it can be concluded that the application of the project-based learning (PjBL) learning model can improve critical thinking skills and learning outcomes of elementary school students.